Study on the Source Profile Characteristics of Carbon Plant - Sen Li; Danni Liang; Jianhui Wu (Atmosphere, 2022)
In the background of carbon neutrality, carbon emissions are basked in the attention. As a significant source of carbon emissions, the emission characteristics of carbon plant should be known. Particulate matter in flue gas was collected in a carbon plant in Tongliao. The chemical components in PM10 and PM2.5 were analyzed, and source profile of carbon plant was established. The results showed that the mass fractions of EC, Ca, Ca2+, S, Al, Si and Fe were higher in particles than other components. The chemical marker of carbon plant was EC, and the trace carbonaceous components of carbon plant were EC1 and EC2, which were very different from other carbon emission sources. In the absence of other chemical composition information, eight carbonaceous components can be used to identify the sources of particle.